Pakistan’S Aggregate And Sectoral Trade Costs Estimations: Evaluating Trade Policies And Institutional Quality - Saqib, Abdul (2024)
This thesis examines trade costs in pakistan, focusing on sectoral and partner-specific asymmetries to reveal their impact on pakistan's trade performance. It also assesses the impact of key trade policies, including applied tariffs, non-tariff barriers and trade agreements; and institutional factors including climate change, economic policy uncertainty, exchange rate volatility, institutional distance, and cultural distance on directional trade costs across sectors. Despite advanced methodologies and available trade data, the literature lacks comprehensive insights into pakistan's directional trade costs. Therefore, rigorous estimations are essential to determine the extent of these costs and understand the underlying factors driving these trade costs. This thesis employs a two-step methodology. In the first step, it applies the generic gravity trade model by egger et al. (2021) to estimate directional trade costs across 32 goods and services sectors with 62 trade partners. In the second stage, these directional trade costs are regressed against trade policies and institutional factors across six models (three for goods and three for services). This analysis uses a poisson pseudo maximum likelihood estimator with high-dimensional fixed effects to account for pair-specific, sector, and time fixed effects and to address issues like heteroskedasticity. The first-stage analysis reveals high and steady trade costs in pakistan, with export costs exceeding import costs. Trade costs are relatively lower with regional partners like sri lanka and maldives but higher with major partners such as the uk and us.